Service-learning for diverse communities : critical pedagogy and mentoring English learners - Purmenbnsky, Kerry L. (Emerald Publishing Limited, 2020)
Service-Learning for Diverse Communities: Critical Pedagogy and Mentoring English Learners (2nd Edition) provides a foundation for understanding service-learning (SL) practices for those working with English Learners or pre-service teachers who have ELs in their classroom. Through three distinct parts, this text guides the reader through the core values of SL and provides specific examples and models of SL practices with ELs in the classroom and encourages leadership and advocacy in the school community. This book contributes to the understanding of SL models and how this educational approach to learning can enhance understanding of English Learners in the community.In this new edition, there are many critical updates to research practices and application. The book updates all chapters related to pedagogical practices, TESOL Standards, Critical Pedagogy, and Assessment. In addition to updating the TESOL Standards, the WIDA Standards have been added and incorporated into current SL practices. Two additional chapters focus on infusing technology into service-learning, discussing Digital Badging in assessment and Virtual Tutoring models. English learner needs are expanded to include Dual Language as an important model for teaching. The last chapter presents a compelling argument for instructors who utilize service-learning in their classrooms to participate in a service-learning opportunity as a student to gain insight into the student service learning experience.
Includes index.
Keywords: English language -- Study and teaching -- Foreign speakers.; Teachers -- Training of.; Critical pedagogy.; Education -- Vocational & Technical.; Industrial or vocational training.; elektronické knihy; electronic books